SEMINAR ROHANI TENTANG SURAT 1 PETRUS 5:7 DI RUMAH SAKIT PONDOK INDAH JAKARTA SELATAN - Harold Walfried Pardede; Gabriel Dhandi (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Healthcare professionals are among those who face high emotional pressure, heavy workloads, and great responsibility in carrying out humanitarian duties. This condisions often lead to stress, mental fatigue, psychological strain. Therefore, it is essential to pay attention to the spiritual well being of healthcare workers. Although hospitals provide various facilities to support the welfare of their staff, spiritual growth also requires serious consideration. Spirituality plays a crucial role in helping individuals adapt, exercise self-control in accordance with moral and spiritual values, and manage stress and mental exhaustion resulting from demanding work, particularly in the healthcare sector. To address this need, the author organized a spiritual seminar at Pondok Indah Hospital, South Jakarta, aiming to provide spiritual guidance and raise awareness among healthcare workers about the importance of maintaining spiritual life in the workplace. The seminar was met with great enthusiasm, as reflected in the number of questions and active discussions following the presentation. The results indicate that participants ware spiritually strengthened and gained a deeper understanding of the meaning and role of spirituality in their professional and personal lives. Overall, the activity demonstrated that fostering spirituality can serve as an effective means of supporting the emotional resilience and well-being of healthcare workers.